ANXIETY IN HEALTHCARE WORKERS DURING THE COVID-19 PANDEMIC - Lazarevic, Marija ž (Medicinski časopis, 2020)
Introduction: At the time of a pandemic, fear is a common occurrence in those persons who are exposed to direct contact with the affected person or there is a possibility that such risky contact may occur in the future. Objective: The primary objective of the study is to claim the degree of fear and anxiety among medical workers employed in the city of Loznica during the COVID-19 pandemic. The secondary objectives of the study were to determine the significance of the difference in the degree of anxiety in physicians and nurses during a pandemic and to assess the prevalence of psychosomatic reactions by the cardiovascular, gastrointestinal, and respiratory tracts in these subjects. Method: Employed medical workers in the territory of the city of Loznica were given an electronic form of Beck’s questionnaire for determining the degree of anxiety in the days of the epidemic increase and the peak in the number of infected. Research hypotheses H0: All medical staff regardless of education level show equal intensity of fear and anxiety during the COVID-19 epidemic H1: All medical staff regardless of education level show equal intensity of fear and anxiety during the COVID-19 epidemic Results: By analyzing the results, the mean value of the Beck test for the assessment of fear and anxiety was 6.91, which represents a state of low anxiety. The hypothesis was confirmed, ie it was determined that there is a statistically significant difference in the level of fear and anxiety between doctors and nurses, and the dullness of psychosomatic reactions in the subjects was determined. Conclusion: The paper presents the emotional reaction of health workers in the city of Loznica during the pandemic COVID-19. It was determined that fear and anxiety reaction are not present in a significant form. It has also been proven that fear is more significantly present in nurses compared to doctors, and the most common psychosomatic reactions that occur during the period of increasing the number of patients with COVID-19 have been presented.